The Effect of Facial Expression Gymnastics and Oral Motoric Exercise in Supporting Communication in Stroke Patients: A Literature Review - Viona Ardhya Pramita; Fahrun Nur Rosyid (STIKep PPNI Jawa Barat, 2026)
Background: Stroke is a neurological disorder that frequently leads to facial muscle weakness, dysarthria, articulation impairment, and reduced communication ability. Rehabilitative interventions such as facial expression exercises and oral motor exercises are commonly used to stimulate orofacial muscles and support recovery of communication functions. Objective: This literature review aims to analyze the effects of facial expression exercises and oral motor exercises on communication abilities in stroke patients. Methods: A literature search was conducted across PubMed, Scopus, ScienceDirect, CINAHL, and Google Scholar for studies published between 2000 and 2025. Articles were selected based on predefined inclusion criteria, and twelve relevant studies were analyzed using a narrative synthesis approach. Results: The findings indicate that facial expression exercises and oral motor exercises are associated with improvements in facial muscle strength, lip and tongue coordination, articulation clarity, and speech intelligibility. Some studies also report improvements in swallowing function; however, these outcomes are distinct from communication measures. Technology-assisted interventions, including speech therapy applications, show potential as complementary tools, although the evidence remains limited. Conclusion: Orofacial exercises appear to be safe and feasible interventions that may contribute to improved communication outcomes in stroke patients. However, the strength of evidence varies across studies, and further high-quality research is needed before recommending widespread or routine implementation.